Perancangan Sistem Informasi Bank Sampah Berbasis Web Pada Bank Sampah Mandiri RW 4 Kelurahan Lakarsantri - Dava Nabila; Nilam Santika; Maulidah Narastri; Febby Rahmatullah; Ahmad Muhit (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Bank Sampah Mandiri is a waste bank established directly by the community of RW 4 Lakarsantri Village, which is one of the Zero Waste Villages of the Environmental Agency. One of the public services owned by RW 4 Lakarsantri to the community is waste bank management services. In Lakarsantri Village, especially RW 4, the waste bank management system is still manual and not computerized, so there is a need for an information system that can facilitate or streamline the operations of the Waste Bank. In addition, the existing savings book can only record the date and nominal savings. The savings book is considered less effective because the process of recording is very prone to loss and misrecording. To solve these problems, a Waste Bank Information System was developed using the Unified Modeling Language (UML) made for the modeling method, MySQL for the database and PHP for the programming language. With this system in the future, it is hoped that it can help Bank Sampah Mandiri in managing and operating efficiently and safely.